Perception of Advertisement in Visegrad Four Countries - Veronika Gašparíkov; Ľudmila Nagyová; Beáta Rizovová (Polityki Europejskie, Finanse i Marketing)
The importance of marketing communication is still increasing. There are a lot of debates about integration of communication tools that can help to achieve more effective results mostly when companies try to operate internationally. The presented paper provides results of survey conducted within Visegrad Four countries that was aimed to find out differences among young people in the field of advertisement perception. There were almost no statistically significant differences just in the area of Internet advertisement effectiveness where the first position of making electronic purchases due to Internet advertisement is held by Polish respondents.